In depth: UNESCO World Heritage sites: Key to biodiversity conservation - Mila Ibrahimova (The UNESCO Courier, 2023)
Biodiversity loss is a critical issue that threatens the survival of countless species and the stability of our planet’s ecosystems. The issue is of particular concern for UNESCO World Heritage sites, which are representative of more than a fifth of global biodiversity.